IMPLEMENTASI SISTEM PEMBELAJARAN MASA NEW NORMAL SEKOLAH DASAR DI KOTA PADANG - Handayani, Revi; Wiwita, Risma; Ramadhani, Ramadhani; Melshandika, Yola (STKIP Pesisir Selatan, 2022)
This study describes the situation of the New Normal learning period. Anxiety in the community who wants face-to-face learning to be carried out again. The method used is descriptive qualitative research method, namely research that describes the actual conditions. This research is used to analyze events, phenomena, or social realities by including analysis and interpretation of the problems studied. This research is expected to be able to see how the implementation of learning during the new normal is carried out in accordance with the provisions that apply during the covid 19 period that hit the city of Padang. Data obtained from various sources, data collection techniques through instruments carried out by researchers, such as observation, interviews and documentation. Research subjects are informants, namely people who provide a description of the current situation, namely a social situation or social situation which consists of three elements, namely place (palce), actors (actors), and activities (activity) that interact synergistically. Then the analysis and conclusion, the location of this research in the city of Padang. This study sees that in the implementation of the new normal learning period after being online for a long time, it must follow the applicable rules and careful preparation in the midst of the covid 19 virus siege. Considering further that many parents of elementary school students want to return to regular learning face to face. Judging from the results of this study, learning in the new normal period is carried out well if there is cooperation between teachers, students and parents in studying at home. Full guidance for children, and the readiness of parents to take their time and continue to carry out health protocols as a condition for face-to-face learning to be reopened